Analisis Penggunaan E-wallet dan Dampaknya Terhadap Perilaku Konsumtif Mahasiswa Universitas Wahid Hasyim Semarang - Neisella, Harum; Pratiwi, Ratih (IKRAITH-EKONOMIKA, 2026)
ABSTRAK Penelitian ini dilakukan untuk menganalisis penggunaan e-wallet dan impaknya pada perilakukonsumtif mahasiswa Universitas Wahid Hasyim Semarang. Sample penelitian adalah mahasiswaaktif yang melalui aktivitas sehari-hari menggunakan e-wallet. Penelitian ini menggunakan metodependekatan kualitatif deskriptif melalui wawancara mendalam, dilengkapi tinjauan pustakapenggunaan e-wallet dan perilaku konsumtif pada berbagai penelitian. Berdasarkan hasilpenelitian, diketahui bahwa e-wallet dapat memberi kemudahan, efisiensi, dan kecepatan pada segitransaksi, tetapi dapat pula memicu tingkat aktivitas konsumtif erkek mahasiswa, terutama melaluipembelian impulsif terhadap promo. ABSTRACT This study aims to study the use of e-wallets and its impact on consumptive behavior of studentsof Universitas Wahid Hasyim Semarang. The participants of this study are active students who arecurrently using e-wallets actively in daily life. This study employed a qualitative descriptivemethod in the form of depth interview helped with a study of literature of previous studies on theuse of e-wallets and consumptive behavior. The findings indicate that the use of e-wallets providesenormous benefits of convenience, rapidity, and transaction effectiveness, but also facilitates theemergence of consumptive behavior of students, particularly through impulsive buys fostered bypromotions, cashbacks, and discounts. Besides, the study proves to show that the impact of the useof e-wallets is not definitive, as students showing higher self-control are found to use themrationally and for necessary needs, and students with poor self-control are easily prone toconsumptive behavior excessively. Therefore, the use of e-wallets should not be made a scapegoatfor consumptive behavior, but rather as financial technology tools whose impact is mostlydependent on the person concerned's self-control, and it becomes essential to foster awareness andfinancial discipline among students to provide maximum benefit from using e-wallets withoutcausing any negative effect on personal financial management.